2021
DOI: 10.1038/s41467-021-24237-y
|View full text |Cite
|
Sign up to set email alerts
|

Observation of current-induced switching in non-collinear antiferromagnetic IrMn3 by differential voltage measurements

Abstract: There is accelerating interest in developing memory devices using antiferromagnetic (AFM) materials, motivated by the possibility for electrically controlling AFM order via spin-orbit torques, and its read-out via magnetoresistive effects. Recent studies have shown, however, that high current densities create non-magnetic contributions to resistive switching signals in AFM/heavy metal (AFM/HM) bilayers, complicating their interpretation. Here we introduce an experimental protocol to unambiguously distinguish c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…Figure 4 shows the Néel vector oscillation amplitude excited by SOT. Here, the ac electrical current is chosen large but achievable in experimentit is sufficiently small to prevent non-magnetic phenomena, such as electromigration [38], but is not far from this limit. The amplitude of Mode 1 is larger than the one of Mode 2 and is weakly dependent on the field in the studied range.…”
Section: Comparison With Alternative Drivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the Néel vector oscillation amplitude excited by SOT. Here, the ac electrical current is chosen large but achievable in experimentit is sufficiently small to prevent non-magnetic phenomena, such as electromigration [38], but is not far from this limit. The amplitude of Mode 1 is larger than the one of Mode 2 and is weakly dependent on the field in the studied range.…”
Section: Comparison With Alternative Drivesmentioning
confidence: 99%
“…However, manipulation of AFM order is a more complex task than in ferromagnets due to the high exchange interaction, making it hard to manipulate them by magnetic fields. Recent experiments have demonstrated that the Néel vector dynamics can be driven by electrical currents via spin-orbit torque (SOT) effects [32][33][34][35][36][37][38]. This is especially important for the implementation of AFMs in hybrid CMOS/spintronic circuits.…”
Section: Introductionmentioning
confidence: 99%
“…In an AFM with two equivalent sublattice magnetizations denoted by M A and M B oriented antiparallel, | M A | = | M B | = M 0 is the magnitude of the sublattice magnetization; the normalized AFM Néel vector (order parameter) is given by l = ( M A – M B )/(2 M 0 ) . Electrical manipulation of the AFM Néel vector with the prospect of encoding information was achieved in various AFM compounds, such as CuMnAs, Mn 2 Au, Mn 3 Pt, , Mn 3 Sn, IrMn 3 , NiO, and CoO, via a relativistic mechanism, namely, Néel order spin–orbit torque (SOT)likely without invoking heat or magnetic fields. In strong contrast, recent experiments showed that significant amounts of charge current densities (≥4 × 10 7 A/cm 2 ) beyond the linear ohmic regime of the devices are needed to switch the Néel vector (or the local AFM domains). The power efficiency, the physical mechanism of switching, and the efficiency of the electrical detection method for validating the current-induced microscopic switching of the AFM domains are currently under investigation. Moreover, recent work based on NiO/Pt bilayer devices revealed a current-induced purely thermomagnetoelastic switching mechanism …”
Section: Introductionmentioning
confidence: 99%
“…5 In an AFM with two equivalent sublattice magnetizations denoted by M A and M B oriented antiparallel, |M A | = |M B | = M 0 is the magnitude of the sublattice magnetization; the normalized AFM Neél vector (order parameter) is given by l = (M A − M B )/(2M 0 ). 6 Electrical manipulation of the AFM Neél vector with the prospect of encoding information was achieved in various AFM compounds, such as CuMnAs, 2 Mn 2 Au, 7 Mn 3 Pt, 5,8 Mn 3 Sn, 9 IrMn 3 , 10 NiO, 11 and CoO, 12 via a relativistic mechanism, namely, Neél order spin−orbit torque 13 (SOT)likely without invoking heat or magnetic fields. In strong contrast, recent experiments showed that significant amounts of charge current densities (≥4 × 10 7 A/cm 2 ) beyond the linear ohmic regime of the devices are needed to switch the Neél vector (or the local AFM domains).…”
Section: Introductionmentioning
confidence: 99%
“…Electric control of magnetic order in antiferromagnets has raised prospects for realizing high-speed and highdensity magnetoelectric devices using materials with zero net magnetization [1][2][3][4][5][6]. The switching of the order parameter in antiferromagnets is achieved by either injecting spin currents from an adjacent heavy metal layer or current-induced spin-orbit torques intrinsic to noncentrosymmetric crystals [7].…”
mentioning
confidence: 99%